Is there an age pattern in the treatment of AMI? Evidence from Ontario - Michel Grignon; Byron G. Spencer; Li Wang (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2010)
In this article we analyse the rates at which those admitted to hospital with acute myocardial infarction (AMI) receive aggressive treatment, assess how those rates have changed over time, and ask whether there is evidence of age discrepancies. Estimates made on the basis of data from an administrative database that includes discharges from all acute care hospitals in Ontario for selected years, from 1995 to 2005, indicate that there are strong and persistent age patterns in the application of medical technology. Results showed that to be true even after controlling for the higher rates of co-morbidities among older patients and variations across hospitals in practice patterns.
Keywords: I11; 330; treatment of AMI; age pattern; Gesundheitsversorgung; Krankenhaus; Altersgruppe; Kanada